Non-thermal plasma causes Pseudomonas aeruginosa biofilm release to planktonic form and inhibits production of Las-B elastase, protease and pyocyanin - Kašparová, Petra; Vaňková, Eva; Paldrychová, Martina; Svobodová, Alžběta; Hadravová, Romana; Jarošová Kolouchová, Irena; Masák, Jan; Scholtz, Vladimir (Frontiers in Cellular and Infection Microbiology, 2022)
The increasing risk of antibiotic failure in the treatment of Pseudomonas aeruginosa infections is largely related to the production of a wide range of virulence factors. The use of non-thermal plasma (NTP) is a promising alternative to antimicrobial treatment. Nevertheless, there is still a lack of knowledge about the effects of NTP on the virulence factors production. We evaluated the ability of four NTP-affected P. aeruginosa strains to re-form biofilm and produce Las-B elastase, proteases, lipases, haemolysins, gelatinase or pyocyanin. Highly strains-dependent inhibitory activity of NTP against extracellular virulence factors production was observed. Las-B elastase activity was reduced up to 82 % after 15-min NTP treatment, protease activity and pyocyanin production by biofilm cells was completely inhibited after 60 min, in contrast to lipases and gelatinase production, which remained unchanged. However, for all strains tested, a notable reduction in biofilm re-development ability was depicted using spinning disc confocal microscopy. In addition, NTP exposure of mature biofilms caused disruption of biofilm cells and their dispersion into the environment, as shown by transmission electron microscopy. This appears to be a key step that could help overcome the high resistance of P. aeruginosa and its eventual elimination, for example in combination with antibiotics still highly effective against planktonic cells.